A Modified Thyroid Imaging Reporting and Data System (mTI-RADS) For Thyroid Nodules in Coexisting Hashimoto’s Thyroiditis - Zhou, Hang (Sci Rep, 2016)
To develop a conventional ultrasound (US) modified Thyroid Imaging Reporting and Data System (mTI-RADS) to stratify the malignancy risk of thyroid nodule in coexisting Hashimoto’s thyroiditis (HT). The study included 138 malignant and 292 benign thyroid nodules confirmed by cytological or histopathological results. The risk score (RS) for each significant US feature was estimated by multiplying corresponding regression coefficient and the total score for each nodule was defined as the sum of these individual scores. The mTI-RADS was established according to the total RS and divided into category 3, 4a, 4b, 4c and 5. Marked hypoechogenicity, taller-than-wide shape, poorly-defined margin, microcalcification or macrocalcification and halo sign absence were statistically significant US features in prediction of thyroid malignancy (all p < 0.05). The total RS for each nodule was defined as following: RS = 2.1× (if marked hypoechogenicity) + 1.2× (if taller-than-wide shape) + 1.7× (if no halo sign) + 0.6× (if poorly-defined margin) + 1.2× (if microcalcification or macrocalcification). The malignancy rates in mTI-RADS category 3, 4a, 4b, 4c and 5 nodules were 3.7%, 19.3%, 38.1%, 62.7% and 94.1%, respectively, with significant differences among different categories (P < 0.001). The mTI-RADS category may facilitate subsequent treatment management in HT patients.